Factors Affecting College Students' Entrepreneurial Intention - hafidza nash'ul amrina; Hasan Bisri (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: The high unemployment rate triggers everyone to set up a small and medium business. Educated people tend not to be interested in pursuing entrepreneurship. This study aims to determine the effect of entrepreneurship education, family environment, income expectations on student entrepreneurial intention. Design/methodology/approach: This research is a quantitative research using the survey method. The population in this study was active students at STIE Cendekia Bojonegoro in 2020 with 427. With the Slovin formula approach, 206 students were assigned as research respondents, where the sample was taken using the Simple Random Sampling technique. Findings: Research data collection is done through the distribution of questionnaires. The data analysis technique in this study used a multiple linear regression test. The analysis results found that the Family Environment variable had no significant effect on entrepreneurial intention. The variables of Entrepreneurship Education and Income Expectations had a positive impact on entrepreneurial intention. Originality/value: This Paper is original Paper type: Research paper